(untitled) (Current Horticulture, 2024)
The experiment was conducted to project climatic changes in major yam-growing environments and also calibrated and evaluated the eco crop model to study the impact of 2030 climate change on yam climate suitability in major yam-growing environments in India. The current climate and future climate projections of 22 GCMs from the SRES-A1B emission scenario were used. The projected change in annual mean temperature and total annual precipitation in yam-growing areas ranged from 0.9 to 1.3°C and from 9 to 128 mm respectively. The calibrated data were used to constrain the eco crop model to find out the suitability of current and future climatic conditions. The results of projected climate change over the Indian yam-growing areas using 22 GCMs of SRES A1B emission scenario revealed that change in suitability will be in the range of -2.04 to 23.5 per cent.